2020
DOI: 10.1002/cyto.b.21958
|View full text |Cite
|
Sign up to set email alerts
|

Sudden blast phase in pediatric chronic myeloid leukemia‐chronic phase with abnormal lymphoid blasts detected by flow cytometry at diagnosis: Can it be considered a warning sign?

Abstract: Background: Inconclusive knowledge persists regarding the course of chronic myeloid leukemia-chronic phase (CML-CP) patients with detectable abnormal blasts by flowcytometry at diagnosis. The 2016 WHO classification is not specific regarding subclassification of CML with <10% abnormal B-lymphoid blasts (ABLB), and suggests these patients often show rapid progression. We report the clinical course of pediatric CML-CP patients who had detectable abnormal blasts by flow-cytometry at baseline. Methods:Retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
7
1
Order By: Relevance
“…To date there have been 18 reported cases of abnormal lymphoblasts in CML-CP [6][7][8][9]. There is an overall high rate of transformation reported with 6/18 (33%) progressing to blast phase with follow-up of 1-67 months despite all patients receiving treatment with TKI therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date there have been 18 reported cases of abnormal lymphoblasts in CML-CP [6][7][8][9]. There is an overall high rate of transformation reported with 6/18 (33%) progressing to blast phase with follow-up of 1-67 months despite all patients receiving treatment with TKI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…As CML-CP is characterised by proliferation of predominantly granulocytes and granulocytic precursors without immunophenotypic aberrancy or maturation arrest, flow cytometry has been considered to be of limited utility in this phase of disease. However, in cases where flow cytometry has been performed, there are reports of detection of abnormal lymphoblast populations with conflicting data on the subsequent risk of development of blast phase [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with more limited data that exists on the potential diagnostic utility of immunophenotyping in MPN, HES, or the altered proliferation profiles in these and other, myeloid neoplasms (Shameli et al, 2020;Ouyang et al, 2015;Herborg et al, 2018;Matarraz et al, 2012;Matarraz et al, 2011). In this issue of Cytometry B six original research papers and a case report have used flow cytometry to study MDS, MDS/MPN, MPN and HES (Shestakova et al, 2021;Davydova et al, 2021;Mestrum et al, 2021;Panda et al, 2021;Vijayasekharan et al, 2021;Hu et al, 2021;Espasa et al, 2021). In the first of these six papers, Shestakova et al (2021) explored the utility of automated leucocyte parameters including cell volume, conductivity and light scatter properties (VCS parameters) as assessed in an automated hematological analyzer, as a read-out for dysplastic MDSassociated features.…”
Section: Flow Cytometry In Myeloid Neoplasmsmentioning
confidence: 99%
“…Overall, 9 patients showed blasts with a CD117 hi CD34 het HLADR ‐ /lo CD203c + immature mast cell‐associated immunophenotype, supporting the potential existence a small percentage of underdiagnosed myelomastocytic leukemia cases; diagnosis of these nine patients corresponded to CML at any phase of the disease (n=4), to newly diagnosed and secondary AML (n=4) and to one chronic myelomonocytic leukemia, whose features are described in detail in the manuscript (Panda et al, 2021). In the fifth paper of this series of manuscripts on myeloid neoplasias, Vijayasekharan et al (2021) report on a retrospective analysis of the value of identifying a population of haematopoietic precursor cells with mixed‐lineage phenotype in a series of 12 pediatric patients diagnosed with chronic phase CML. Preliminary results reported for the 12 CML patients included in this study showed that among 5 cases in which precursor cells with a mixed B‐myeloid (B/M or B/T/M) phenotype were detected a greater frequency (3/5 patients) of progression to acute leukemia associated with Imatinib‐resistant gene mutations was observed vs. that found in cases with aberrant myeloid‐only precursors (0/5 cases), suggesting immunophenotyping of pediatric CML patients during chronic phase of the disease could contribute to identify patients at higher risk of progression to acute leukemia with Imatinib‐resistant mutations (2021).…”
Section: Flow Cytometry In Myeloid Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation